A Pair of Hydrogen‐Bonded Cobalt(II) Complexes Showing the Proton Conduction and Spin Crossover Property - Liu, Fu‐Bin; Shang, Meng‐Jia; Lu, Han‐Han; Li, Jing; Kong, Cong; Zhang, Wen‐Jing; Meng, Yin‐Shan; Liu, Tao (European journal of inorganic chemistry, 2025)
Achieving high proton conductivity in spin‐crossover (SCO) compounds is promising for the development of magnetoelectric and spintronics devices. In this work we designed two spin‐crossover and proton‐conductive bifunctional Co(II) compounds, [Co(Pyrimidine‐terpy)2](BF4)2⋅2H2O (1⋅2H2O; Pyrimidine‐terpy=4′‐(5‐pyrimidinyl)‐2,2′:6′,2“‐terpyridine) and [Co(Pyrimidine‐terpy)2](ClO4)2⋅2H2O (2⋅2H2O). Both compounds undergo the typical spin transitions and have a hydrogen‐bonding network consisting of anions with solvent water molecules. At 353 K and under 95 % relative humidity, the proton conductivity of 1⋅2H2O was 1.9×10−4 S cm−1 and that of 2⋅2H2O was 7.5×10−5 S cm−1. The activation energy analysis indicates that the proton conduction of 1⋅2H2O follows the Vehicle mechanism in the temperature range of 303–318 K, while the Grotthuss mechanism plays a dominant role in the higher temperature range of 323–353 K. Additionally, 2⋅2H2O also follows the Grotthuss mechanism in the temperature range of 338–353 K. This study provides new guidelines for the design of novel SCO molecular materials with proton conduction functionality. A Pair of Hydrogen‐Bonded Cobalt(II) Complexes showing the Proton Conduction and Spin Crossover Property is reported. A pair of hydrogen‐bonded cobalt(II) complexes was constructed by modified terpyridine ligands. Both of them showed the temperature‐dependent proton conduction and spin crossover properties, representing a new type of SCO molecular materials with proton conduction functionality.